2001
DOI: 10.1177/107319110100800304
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of MMPI-2 Suicide Items for Assessing Suicidal Potential: Development of a Suicidal Potential Scale

Abstract: The assessment of suicidal potential is one of the most challenging and stress-inducing tasks facing clinicians. Studies that have attempted to identify specific MMPI codetypes, scales, or individual items predictive of completed suicide have produced inconsistent findings. This study focused on the relationship between the six most direct MMPI-2 suicide items (Items 150, 303, 506, 520, 524, and 530) and verbally reported history of suicidal ideation and behavior among a sample of psychotherapy outpatients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
20
0
2
Order By: Relevance
“…Although semi-structured interviews may afford clinicians the flexibility to ask clarifying questions, evidence suggests that individuals may be more open to disclosing information regarding suicidality (Glassmire, Stolberg, Greene, & Bongar, 2001) and other psychiatric symptoms (Garb, 2007; Tourangeau & Yan, 2007; Turner et al, 1998) on self-report or computer-based measures. Therefore, results from this type of study would be particularly illuminating.…”
Section: Discussionmentioning
confidence: 99%
“…Although semi-structured interviews may afford clinicians the flexibility to ask clarifying questions, evidence suggests that individuals may be more open to disclosing information regarding suicidality (Glassmire, Stolberg, Greene, & Bongar, 2001) and other psychiatric symptoms (Garb, 2007; Tourangeau & Yan, 2007; Turner et al, 1998) on self-report or computer-based measures. Therefore, results from this type of study would be particularly illuminating.…”
Section: Discussionmentioning
confidence: 99%
“…The Suicide Potential Scale (SPS; Glassmire et al, 2001) is a six question scale assessing suicidal behavior using questions from the MMPI-2. As indicated, this is not a standard scale on the MMPI-2 and is not included in the administration manual.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is not a standard MMPI-2 scale or included in the MMPI-2 manual, the Suicidal Potential Scale (SPS) was developed by Glassmire and colleagues (2001) for the MMPI-2 and included six critical items related to suicidal behavior and suicidal intent (Glassmire, Stolberg, Greene, & Bongar, 2001). Results from Glassmire and colleagues (2001) indicated that participants were more likely to report suicidal ideation or behavior on the MMPI-2 than during a telephone intake interview and that the SPS was a reliable assessment of suicidal behavior. Another scale no longer available on the MMPI-2-RF is the Suicidal Ideation (DEP4) content component scale that assessed recent suicidal ideation (Graham, 2006).…”
mentioning
confidence: 99%
“…Kao takav, posebno se pokazao kao koristan u dijagnostici i diferencijalnoj dijagnostici širokog spektra psihopatologije (23,27). Ipak, na polju suicidalnosti u priručnicima za upotrebu MMPI-a nema jasnih preporuka za detekciju ovog fenomena.…”
Section: ) Poveznost Između Sbq-unclassified
“…Ipak, na polju suicidalnosti u priručnicima za upotrebu MMPI-a nema jasnih preporuka za detekciju ovog fenomena. Upravo to potrkepljuju i opreč-ni rezultati koji su dobijani pri ispitivanjima korisnosti ovog instrumenta u određivanju stepena suicidalnosti ili pak visine suicidalnog rizika (27). Sa jedne strane, izdvajaju se istraživanju koja ukazuju značajne povezanosti.…”
Section: ) Poveznost Između Sbq-unclassified